2019
DOI: 10.1101/783571
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PlasClass improves plasmid sequence classification

Abstract: AbstractBackgroundMany bacteria contain plasmids, but separating between contigs that originate on the plasmid and those that are part of the bacterial genome can be difficult. This is especially true in metagenomic assembly, which yields many contigs of unknown origin. Existing tools for classifying sequences of plasmid origin give less reliable results for shorter sequences, are trained using a fraction of the known plasmids, and can be diff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 8 publications
0
44
0
Order By: Relevance
“…We compared PCS versus PlasClass (Pellow, Mizrahi, and Shamir 2020) , a recent method that also fits a logistic regression but uses k-mers of length 3-7 as features, in their ability to classify the 10kb sequences. We did not compare with other k-mer methods (Krawczyk, Lipinski, and Dziembowski 2018;Zhou and Xu 2010) because the PlasClass study reported better performance than them.…”
Section: Pcs: a State-of-the-art Plasmid Classifier System Based On Gmentioning
confidence: 99%
“…We compared PCS versus PlasClass (Pellow, Mizrahi, and Shamir 2020) , a recent method that also fits a logistic regression but uses k-mers of length 3-7 as features, in their ability to classify the 10kb sequences. We did not compare with other k-mer methods (Krawczyk, Lipinski, and Dziembowski 2018;Zhou and Xu 2010) because the PlasClass study reported better performance than them.…”
Section: Pcs: a State-of-the-art Plasmid Classifier System Based On Gmentioning
confidence: 99%
“…Many bioinformatic tools have been recently developed to overcome this challenge in short-read sequencing. Examples of them are PlasmidFinder, cBar, PLACNET, (meta)plasmidSPAdes, recycler, plasflow, MOB-suite, mlplasmids, plaScope, gplas, plasClass, plasGUN,SCAPP, metaviralSPAdes ( Zhou and Xu, 2010 ; Carattoli et al., 2014 ; Rozov et al., 2017 ; Vielva et al., 2017 ; Arredondo-Alonso et al., 2018 ; Arredondo-Alonso et al., 2020 ; Krawczyk et al., 2018 ; Robertson and Nash, 2018 ; Royer et al., 2018 ; Antipov et al., 2019 , 2020 ; Fang et al., 2020 ; Pellow et al., 2020a , Pellow et al., 2020b ; Pellow et al., 2020 , 2020 ). These tools identify plasmids and viruses in metagenomic samples or bacterial isolates in a variety of ways, ranging from the simpler approach of blasting against a plasmid database (PlasmidFinder, MOB-suite) to the use of more complex deep neural networks (cBar, PlasFlow).…”
Section: Methods For Mobile Genetic Elements Analysis In Environmentamentioning
confidence: 99%
“…By default, we use PlasClass (Pellow et al, 2019) to annotate each node in the assembly graph with a plasmid score. PlasFlow (Krawczyk et al, 2018) scores are also supported.…”
Section: Plasmid Score Annotationmentioning
confidence: 99%
“…The peeling may reduce coverage of each involved node, or remove it altogether. In SCAPP the assembly graph is annotated with plasmid-specific genes and a plasmid score based on a plasmid sequence classifier (Pellow et al, 2019). In the annotated assembly graph we prioritize circular paths that include plasmid genes and highly probable plasmid sequences.…”
Section: Introductionmentioning
confidence: 99%